An experimental and modeling study of the oxidation of n‐heptane, ethylbenzene, and n‐butylbenzene in a jet‐stirred reactor at pressures up to 10 bar. Issue 12 (28th August 2020) - Herbinet, Olivier; Husson, Benoit; Le Gall, Hervé; Battin‐Leclerc, Frédérique
Abstract: In the context of better understanding pollutant formation from internal combustion engines, new experimental speciation data were obtained in a high‐pressure jet‐stirred reactor for the oxidation of three molecules, which are considered in surrogates of diesel fuel, n ‐heptane, ethylbenzene, and n‐ butylbenzene. These experiments were performed at pressures up to 10 bar, at temperatures ranging from 500 to 1 100 K, and for a residence time of 2 s. Based on results previously obtained close to the atmospheric pressure for the same molecules, the pressure effect on fuel conversion and product selectivity was discussed. In addition, for the three fuels, the experimental temperature dependence of species mole fractions was compared with simulations using recent literature models with generally a good agreement. For n‐ heptane, the obtained experimental data, at 10 bar for stoichiometric mixtures, included the temperature dependence of the mole fractions of the reactants and those of 21 products. Interestingly, the formation of species previously identified as C7 diones was found significantly enhanced at 10 bar compared with lower pressures. The oxidation of ethyl‐ and n ‐butylbenzenes was investigated at 10 bar for equivalence ratios of 0.5, 1, and 2. The obtained experimental data included the temperature dependence of the mole fractions of the reactants and those of 13 products for the C8 fuels and of 19 products for the C10 one. For ethylbenzene under stoichiometric conditions, the pressure dependence (from 1 to 10 bar) of species mole fraction was also recorded and compared with simulations with more deviations obtained than for temperature dependence. For both aromatic reactants, a flow rate analysis was used to discuss the main pressure influence on product selectivities.